Respuesta :
Answer:
8y=-6 or 4y=-3
Step-by-step explanation:
We are given two equations
[tex]x+6y=9\\and\\-x+2y=-15[/tex]
In order to add the equations, the left hand side of one equation will be added to the left hand side of second equation. similarly, the right hand side of first equation will be added to the right hand side of the equation so,
[tex]x+6y+(-x+2y)=9+(-15)\\Combining\ alike\ terms\\x+6y-x+2y=9-15\\6y+2y=-6\\8y=-6\\Can\ also\ be\ written \ as\\4y=-3[/tex]
Answer:
The resultant equation is 8y = -6
Step-by-step explanation:
To get the system of equation that will results from adding the statement, we will follow the steps below;
x+6y=9 -------------------------------------------------------------------------------(1)
-x+2y=-15-------------------------------------------------------------------------------(2)
Adding equation (1) and equation(2), we will have;
(1-1)x + (6+2)y =(9-15)
x variable will go away
8y =-6
The resultant equation is 8y = -6